In-circuit testing - Buckroyd, Allen (Butterworth-Heinemann, 1994)
In-Circuit Testing discusses what an in-circuit test (ICT) is and what it can and cannot do. It answers many questions on how tests are actually carried out, with the benefits and drawbacks of the techniques. The emphasis throughout is towards practical problem solving, and many of the examples used are of surface mount printed circuit boards (PCBs). The book contains separate chapters on application-fitting ICT into a typical test strategy and into the manufacturing environment. The buying decision is fully explored-choice of system, initial and ongoing costs, and preparation of the financial.